👤
Ioanaa447
a fost răspuns

3(2+-3)=5-2(2x+1)
ajutor va rogg dau coroana


Răspuns :

Răspuns:

3(2+-3)=5-2(2x+1)

3×(-1)=5-4x-2

-3=5-4x-2

-3+2-5=-4x

-6=-4x=>x=6/4=>x=3/2

Răspuns: [tex]\red{\bf x = \dfrac{3}{2}}[/tex]

Explicație pas cu pas:

[tex]\bf 3\cdot(2-3)=5-2\cdot(2x+1)[/tex]

[tex]\bf 6-9=5-4x-2[/tex]

[tex]\bf 6-9=3-4x[/tex]

[tex]\bf 6-9+4x=3[/tex]

[tex]\bf 4x=3-6+9[/tex]

[tex]\bf 4x=6[/tex]

[tex]\bf x=\dfrac{6^{(2}}{4} \implies \red{\boxed{\bf x = \dfrac{3}{2}}}[/tex]

==pav38==

Baftă multă !